2017
DOI: 10.3389/fpsyg.2017.01989
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Regional Gray Matter Volume of Social Exclusion Regions and Personal Self-Esteem Is Moderated by Collective Self-Esteem

Abstract: According to sociometer theory, self-esteem is an internal monitor of positive social bonds to others. Social exclusion can break or threaten social bonds, which might be reflected by the brain structure of social exclusion regions. Thus, self-esteem might be influenced by structurally individual differences in these regions. It has been suggested that self-esteem can be divided into personal (PSE) and collective (CSE) self-esteem and CSE can bring individuals many benefits, such as acceptance, belonging, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For example, Blackhart et al ( 2009 ) found that social exclusion did not affect self-esteem, although it did elicit some negative emotions. The results from neuroimaging studies also showed that the dACC was not related to self-esteem (Wu et al, 2017 ) or the distress elicited by social exclusion (Kross et al, 2007 ), but self-esteem was related to the functions of the dACC when processing self-related stimuli (Yang et al, 2012 ) and negative feedback on the self (Peng et al, 2019 ). However, it should be noted that self-esteem can be further divided into contingent and true self-esteem (Deci and Ryan, 1995 ; Ryan and Deci, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Blackhart et al ( 2009 ) found that social exclusion did not affect self-esteem, although it did elicit some negative emotions. The results from neuroimaging studies also showed that the dACC was not related to self-esteem (Wu et al, 2017 ) or the distress elicited by social exclusion (Kross et al, 2007 ), but self-esteem was related to the functions of the dACC when processing self-related stimuli (Yang et al, 2012 ) and negative feedback on the self (Peng et al, 2019 ). However, it should be noted that self-esteem can be further divided into contingent and true self-esteem (Deci and Ryan, 1995 ; Ryan and Deci, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-esteem is an attitude based on positive and negative self-evaluations (Rosenberg, 1965 ; Yang et al, 2016 ; Wu et al, 2017 ). Self-concept clarity refers to the degree to which the contents of self-concept are clearly and confidently defined, internally consistent, and temporarily stable (Campbell et al, 1996 ; Findley, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The former is the overall positive evaluation and acceptance of individuals to themselves [ 25 , 26 ], while the latter is the individual’s evaluation and perception of the value of the group he or she belongs to, which emphasizes a sense of collective value, respect and belonging [ 27 ]. In the context of Chinese collectivist culture, self-esteem, with its strong collective and social overtones, has also become a focus of research [ 28 , 29 ]. Existing studies also indirectly support the mediating path of school climate - collective self-esteem - academic burnout.…”
Section: Introductionmentioning
confidence: 99%